BS EN 62841-3-10 AMD1. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-10. Particular requirements for transportable cut-off machines (22nd January 2021) - British Standards Institution,
No abstract available